Research hotspots and trend analysis of cell transplantation in traumatic spinal cord injury: a bibliometric and visualized analysis - Guo, Yuhuai; Gao, Bowen; Sun, Shilin; Li, Jianuo; Lv, Xiaolin; Yin, Hongna; Sun, Zhongren; Cai, Shuo (Frontiers in Pharmacology, 2023)
Background: Cell transplantation therapy has shown great potential in the reconstruction of damaged spinal cords and promoting functional recovery. However, there is a lack of frontiers and futures analysis in the study of cell transplantation in TSCI. Methods: We used CiteSpace, VOSviewer and biblilometrix R package to perform bibliometric analysis on cell transplantation in TSCI from 2013 to 2023. Bibliometric records were extracted from English articles and reviews from the Web of Science core collection. Results: The bibliometric analysis included 284 papers published in 154 journals by 1780 authors from 487 institutions in 41 countries and regions. The number of articles published in the past decade has fluctuated slightly, while citations has steadily increased. Mainland China and the United States are the leading countries and regions in this field, with the National Natural Science Foundation of China being the most funded foundation, and the United States being the country with the most funded articles. The University of Toronto in Canada is a prolific institution. Michael G. Fehlings has published the most articles, and D Michele Basso is the most cited author. Cell transplantation is the most published journal, and the Journal of Neurotrauma is the most cited journal. Cell and tissue engineering and clinical neurology are the basic disciplines in this field, and cutting-edge disciplines include developmental biology, biochemistry and molecular biology, and materials science and multidisciplinary. This study also helps scholars understand the current hotspots and future trends in this field. Marrow stromal cells, glial progenitor, and cell therapy are current research hotspots in this field, while nerve regeneration, cell therapy, and the safety of transplantation of transplantation may be potential research directions in the future. Conclusion: Cell transplantation after TSCI is receiving increasing attention. Cell therapy is both the frontier and a possible future trend in TSCI research. In addition, glial progenitor and marrow stromal cells are also current research hotspots. Meanwhile, nerve regeneration and This is a provisional file, not the final typeset article safety of transplantation may be potential research directions. These findings will help further deepen research on cell transplantation for TSCI in scientific work.